(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Social media is a great way to connect with people in your life. The world seeing a rapid technology migration to both higher speed mobile brand networks and the increased adoption of smart phones and connected device. Social media sites have the potential to fundamentally change the character of our social lives both on an interpersonal and community level. Up to date information at fingertips has become the norms to ensure efficiency. Youngsters and students send message or emotions through iPhone or new version of smart phone. Every studenthas to be used smart phone during pandemic periods.The use of these social networking sites or the Internet affects the physical, mental, and spiritual health of the students. Social media has a wide range of effects positive and negative on individuals and society.Students used social media mainly for sharing their assignments, projects and learning experiences with their colleagues. Every parents should advise their children to spend time on E Learning, new skills and modern technologies rather than wasting time on social media likes and shares.